Flags of our father - Eastwood, Clint, 1930-; Speilberg, Steven; Lorenz, Robert; Warner Bros Pictures; Dreamworks Pictures (Universal City, CA : DreamWorks, 2007)
Chronicles one of the bloodiest battles of World War II, focusing on the men who raised the flag at Iwo Jima and were subsequently hailed as heroes and used to raise money for the war effort
Title from title screen
Based on the book by James Bradley with Ron Powers
Actors : Ryan Phillippe, Jesse Bradford, Adam Beach, John Benjamin Hickey
With Malay and Chinese subtitles
Keywords: Bradley, James, -- 1954- -- Film and video adaptations; Powers, Ron -- Film and video adaptations; United States. -- Marine Corps -- Drama; United States. -- Navy -- Drama; Iwo Jima, Battle of, Japan, 1945 -- Personal narratives, American -- Drama; World War, 1939-1945 -- Japan -- Drama; Photographs -- History -- 20th century -- Drama; Marines -- United States -- Drama